POLA KONSUMSI HEDONISME GENERASI MILLENIAL MUSLIM TERHADAP TEORI KONSUMSI DALAM PRESPEKTIF EKONOMI ISLAM - Muthiatu Thoyibah; Muhammad Iqbal Fasa; Suharto (Universitas Muhammadiyah Prof Dr Hamka, 2021)
Islamic consumption theory has the most basic goal of an economy, namely to take blessings and benefits from it. In this study, it aims to find out how the application of consumption patterns among the Muslim millennial generation is in accordance with the consumption pattern of the Islamic economy. Of course, this research will be useful for stakeholders as a material for improvement or suggestions for implementing Islamic economics in their daily lives. The author uses a descriptive type of research and uses a literature study, which is an effort to obtain the necessary materials by reading books and relevant scientific works, including articles published in various print and electronic media. The results show that the current millennial generation is more concerned with the trends they see in social media, one of which is the TikTok application, especially the growing fashion trend. This changes the consumption pattern of the millennial generation not only trying to meet their needs (needs) but also forcing themselves to fulfill what they want (wants). So the Muslim millennial generation should apply Islamic consumption patterns in their lives. The application of this Islamic consumption theory includes ethics and principles that are in accordance with the Qur'an and Hadith. Keywords: Islamic Consumption Theory, Muslim Millennial Generation, Descriptive Analysis